Advances in the domain of 4-amino-3-mercapto-1, 2, 4-triazine-5-ones. Issue 29 (1st March 2016) - Hamama, Wafaa S.; El-Bana, Ghada G.; Shaaban, Saad; Habib, O. M. O.; Zoorob, Hanafi H.
Abstract : This review summarizes results from a literature survey concerning the synthesis and reactions of 4-amino-3-mercapto-1, 2, 4-triazine-5-ones reported by research groups from 1983 to mid. 2015. Abstract : This review summarizes results from a literature survey concerning the synthesis and reactions of 4-amino-3-mercapto-1, 2, 4-triazine-5-ones reported by research groups from 1983 to mid. 2015.